2017
DOI: 10.1590/1806-9282.63.05.407
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biological therapy on body composition of patients with Chron's disease

Abstract: suMMary Study conducted at the Inflammatory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 42 publications
2
26
1
2
Order By: Relevance
“…From the studies included in the meta-analyses, 9 studies reported a significant overall increase in body weight (Franchimont et al, 2005;De Oliveira et al, 2008;Saraceno et al, 2008;Esposito et al, 2009;Di Renzo et al, 2011;Toussirot et al, 2014;Csontos et al, 2016;Dos Santos et al, 2017) and 11 reported a significant increase in BMI (Gisondi et al, 2008;Esposito et al, 2009;Di Renzo et al, 2011;Tan et al, 2013;Mahe et al, 2014;Toussirot et al, 2014;Csontos et al, 2016;Ehsani et al, 2016;Dos Santos et al, 2017). Seven studies reported no significant change in body weight (Marcora et al, 2006;Metsios et al, 2007;Wiedenmann et al, 2008;Popa et al, 2009;Derdemezis et al, 2010;Younis et al, 2013;Ersozlu Bozkirli et al, 2014) and nine reported no significant change in BMI.…”
Section: Summary Of the Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the studies included in the meta-analyses, 9 studies reported a significant overall increase in body weight (Franchimont et al, 2005;De Oliveira et al, 2008;Saraceno et al, 2008;Esposito et al, 2009;Di Renzo et al, 2011;Toussirot et al, 2014;Csontos et al, 2016;Dos Santos et al, 2017) and 11 reported a significant increase in BMI (Gisondi et al, 2008;Esposito et al, 2009;Di Renzo et al, 2011;Tan et al, 2013;Mahe et al, 2014;Toussirot et al, 2014;Csontos et al, 2016;Ehsani et al, 2016;Dos Santos et al, 2017). Seven studies reported no significant change in body weight (Marcora et al, 2006;Metsios et al, 2007;Wiedenmann et al, 2008;Popa et al, 2009;Derdemezis et al, 2010;Younis et al, 2013;Ersozlu Bozkirli et al, 2014) and nine reported no significant change in BMI.…”
Section: Summary Of the Main Resultsmentioning
confidence: 99%
“…Reid and Li propose that TNF-a stimulates differentiated muscle cell protein loss through its activation of nuclear factor (NF)-kB and subsequent upregulation of ubiquitin/proteasome pathway (Reid and Li, 2001;Patel and Patel, 2017). In line with this, five studies using TNF-a inhibitors reported an increase in lean mass (Briot et al, 2005;Briot et al, 2008;Di Renzo et al, 2011;Csontos et al, 2016;Dos Santos et al, 2017).…”
Section: Mechanisms How Tnf-a Inhibitors Might Lead To Weight Painmentioning
confidence: 88%
“…In addition, they also showed that in 12 active CD patients, following the induction protocol with infliximab, FFM increased, albeit not significantly, and PhA normalized. However, Santos et al [20] showed that PhA did not improve after 24 weeks of infliximab therapy in 23 CD patients (p ¼ 0.53), and some differences were observed in BC, with a substantial increase in FM compared to FFM. Our findings did not show any significant differences between CD patients, although both total and segmental PhA were slightly higher, albeit not significantly, in those on biologic therapy compared to the values of patients on conventional therapy or no therapy.…”
Section: Discussionmentioning
confidence: 97%
“…As such, many studies used PhA as a tool for predicting nutritional status as well as for assessing clinical results and/or disease progression in different clinical conditions [15e18]. To date, however, only a few studies [19,20] have assessed impedance parameters to identify and monitor nutritional risk in adults with CD, showing contrasting results.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 23 studies, 11 reported information on body weight changes. Of these, six involved paediatric patients (164 participants) [8,25,33,35,36,40] and five involved adults [21,22,24,39,42]. For paediatrics, SMD calculation was possible for four of the six studies; these four studies were included in the meta-analysis [8,25,33,40].…”
Section: The Effect Of Tumour Necrosis Factor (Tnf)-α Inhibitors On Bmentioning
confidence: 99%